2023
DOI: 10.3390/vaccines11081314
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Serum Perforin and Granzyme during the Acute Phase of SARS-CoV-2 Infection

Abstract: Background: As many SARS-CoV-2 infections are asymptomatic, it could be useful to be able to determine how much time has passed since infection. We explored the changes in the temporal levels of T cell-related proteins (including perforin and granzymes) in the sera of patients with SARS-CoV-2 infection using a commercially available assay. Methods: This study enrolled 36 patients infected with SARS-CoV-2 and 20 healthy control participants. Blood samples were collected at three different times based on the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that natural killer (NK) cells and CD8-positive T cells contribute to virus clearance in COVID-19 patients. 14 , 15 When we measured the cytolytic granules in serum from this patient ( Figure 2 B), high concentrations of perforin and granulysin were detected, suggesting that NK cells and CD8-positive T cells are likely functional in this patient. However, the virus was not eliminated in this patient, suggesting NK cells and CD8-positive T cells alone are insufficient to eliminate the virus under conditions where there are almost no antibodies against the virus.…”
Section: Resultsmentioning
confidence: 84%
“…It has been reported that natural killer (NK) cells and CD8-positive T cells contribute to virus clearance in COVID-19 patients. 14 , 15 When we measured the cytolytic granules in serum from this patient ( Figure 2 B), high concentrations of perforin and granulysin were detected, suggesting that NK cells and CD8-positive T cells are likely functional in this patient. However, the virus was not eliminated in this patient, suggesting NK cells and CD8-positive T cells alone are insufficient to eliminate the virus under conditions where there are almost no antibodies against the virus.…”
Section: Resultsmentioning
confidence: 84%
“…However, it also has several limitations. First, the information of exact timing of SARS-CoV-2 infection is limited ( 33 ). Therefore, the reported anti-N and anti-S IgG titers could have been affected by the time of report.…”
Section: Discussionmentioning
confidence: 99%